Constant value added share analysis: A novel trade decomposition technique with an application to the Philippines - Peter A. G. van Bergeijk; Gina Ledda (Economies, 2024)
This article provides a novel approach to the traditional constant market share (CMS) analysis recognizing the importance of global production networks and fragmentation that necessitate using trade in value added (TiVA) rather than gross trade. We discuss how the components of a CMS analysis need to be (re)interpreted and apply our Constant Value Added Share (CVAS) analysis to the Philippines in the years 1995-2020 using the latest TiVA 2023 dataset (released in November 2023) and compare CMS to CVAS in order to facilitate understanding the contribution of the novel approach. The CVAS analysis finds that while Philippine and world Value Added grew at par, the country lost competitiveness. Traditional CMS suggests a smaller loss of competitiveness. Our approach also identifies specific sectoral weaknesses (i.e., computer and electronics exports) and emerging strengths (technology-related business services) that are unclear in CMS analysis. We argue that Constant Value Added Share analysis is useful for assessing the global value chain performance of other developing countries as well.
Keywords: 330; constant market share; decomposition analysis; developing countries; global value chains; international trade; Philippines; production networks; supply chains; TiVA; value added data